346 Feeding Hempseed Cake Alters the Bovine gut, Respiratory and Reproductive Microbiota. (21st September 2022) - Winders, Thomas; Holman, Devin; Schmidt, Kaycie; Smith, David J; Neville, Bryan W; Dahlen, Carl R; Swanson, Kendall C; Amat, Samat
Abstract: A growing number of studies have investigated the viability of feeding hemp by-products as livestock feedstuffs; however, their impact on livestock microbiomes remains unexplored. Here, we evaluated the effects of feeding hempseed cake (HSC) on the gastrointestinal, respiratory, and reproductive microbiota in beef heifers. Angus-crossbred heifers [19-months old; initial body weight (BW) = 494 ± 10 kg] were fed a corn-based finishing diet (10% forage) containing either 20% HSC (n = 15) or 20% corn distillers grains (Control, n = 16) for 111 days until slaughter. Individual feed intake, feeding behavior and BW were measured throughout the study. Rumen fluid and deep nasopharyngeal swabs (days 0 7, 42, 70 and 98), and vaginal and uterine swabs (at slaughter) were collected, and the microbiota assessed using 16S rRNA gene sequencing. HSC feeding resulted in reduced average daily gain (P = 0.05) without influencing feed intake and feeding behavior (P > 0.05) (reported elsewhere). Sampling time had a significant effect on both ruminal (PERMANOVA: R 2 = 0.39; P < 0.001) and nasopharyngeal (R 2 = 0.18; P < 0.001) microbial community structure. There was also a significant effect of diet on the ruminal (d7– 98; 0.06 ≤ R 2 ≤ 0.12; P < 0.05), nasopharyngeal (d 42; R 2 = 0.18; P < 0.001), and vaginal (R 2 = 0.06; P < 0.01) microbiota. Although microbial richness in the rumen, nasopharynx, vagina, and uterus was not affected (P > 0.05) by HSC feeding, microbial diversity (Shannon diversity) was increased in the rumen (d42-98) but reduced in the uterus of HSC heifers (P < 0.05). The relative abundance of five ruminal genera was enriched, while five vaginal genera were reduced in HSC heifers (P < 0.05). Overall, the results of our longitudinal study suggest that feeding hemp by-products can alter the bovine gut, respiratory and reproductive microbiota.